2006
DOI: 10.1128/aac.00270-06
|View full text |Cite
|
Sign up to set email alerts
|

AG205, a Novel Agent Directed against FabK of Streptococcus pneumoniae

Abstract: AG205 was identified from high-throughput screening as a potent inhibitor of FabK, the enoyl-ACP reductase in Streptococcus pneumoniae. Specific inhibition of lipid biosynthesis in a macromolecular biosynthesis assay and identification of an Ala141Ser substitution in FabK from spontaneous AG205-resistant mutants indicated that AG205 exerts antibacterial activity against S. pneumoniae through the specific inhibition of FabK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The enzymatic reaction proceeds via a Bi-Bi double displacement (or Ping-Pong) mechanism, with the NADH cofactor binding first to the active site and reducing the FMN group, followed by displacement of NAD + by the enoyl substrate, which is reduced by the FMNH 2 group, thereby returning the enzyme to its original state [18]. Inhibitor screening studies that have been performed against the SpFabK enzyme used concentrations for crotonyl-CoA and NADH significantly greater than the reported K m values (200 µM and 400 µM, respectively) [24]. The use of balanced assay conditions, where the assay concentrations of cofactor and substrate are near their K m values, maximizes the chances of finding inhibitors with the broadest diversity in terms of mechanism of inhibition (competitive, noncompetitive, uncompetitive) [25].…”
Section: Resultsmentioning
confidence: 99%
“…The enzymatic reaction proceeds via a Bi-Bi double displacement (or Ping-Pong) mechanism, with the NADH cofactor binding first to the active site and reducing the FMN group, followed by displacement of NAD + by the enoyl substrate, which is reduced by the FMNH 2 group, thereby returning the enzyme to its original state [18]. Inhibitor screening studies that have been performed against the SpFabK enzyme used concentrations for crotonyl-CoA and NADH significantly greater than the reported K m values (200 µM and 400 µM, respectively) [24]. The use of balanced assay conditions, where the assay concentrations of cofactor and substrate are near their K m values, maximizes the chances of finding inhibitors with the broadest diversity in terms of mechanism of inhibition (competitive, noncompetitive, uncompetitive) [25].…”
Section: Resultsmentioning
confidence: 99%
“…Although novel FabI inhibitors targeting S. aureus have been reported by several groups (Heerding et al 2001; Seefeld et al 2001; Ling et al 2004; Kitagawa et al 2007a; Takahata et al 2007; Yum et al 2007), there are only a few reports of FabK inhibitors (Payne et al 2002; Seefeld et al 2003; Zheng et al 2006). We have reported the inhibitor AG205 and more effective FabK inhibitors showing both FabK inhibitory activity and antibacterial activity against S. pneumoniae (Takahata et al 2006; Kitagawa et al 2007b,c). Inhibitors designed to target FabK are attractive as antibiotics against microorganisms that utilize the FabK pathway, in particular, S. pneumoniae .…”
mentioning
confidence: 99%
“…Although an alternative enoyl-ACP reductase, FabK, which displays no significant sequence homology to FabI, was identified in Streptococcus pneumoniae, Enterococcus faecalis and Pseudomonas aeruginosa [8], genomic studies have revealed that most bacteria possess FabI as the sole enoyl-ACP reductase. There are several recent reports of FabI inhibitors with antibacterial activity against S. aureus [9ϳ11], or a novel FabK inhibitor with antipneumococcal activity [12].…”
Section: Introductionmentioning
confidence: 99%